Pathological complete response after neoadjuvant chemotherapy and impact on breast cancer recurrence and survival: a comprehensive meta-analysis - Spring, Laura M. (Clin Cancer Res, 2020)
PURPOSE: While various studies have highlighted the prognostic significance of pathological complete response (pCR) after neoadjuvant chemotherapy (NAT), the impact of additional adjuvant therapy after pCR is not known. EXPERIMENTAL DESIGN: PubMed was searched for studies with NAT for breast cancer and individual patient-level data was extracted for analysis using plot digitizer software. Hazard ratios (HRs), with 95% probability intervals (PIs), measuring the association between pCR and overall survival (OS) or event-free survival (EFS), were estimated using Bayesian piecewise-exponential proportional hazards hierarchical models including pCR as predictor. RESULTS: Overall, 52 of 3209 publications met inclusion criteria, totaling 27,895 patients. Patients with a pCR after NAT had significantly better EFS (HR 0.31, 95% PI: 0.24–0.39), particularly for triple negative (HR 0.18, 95% PI: 0.10–0.31) and HER2+ (HR 0.32, 95% PI: 0.21–0.47) disease. Similarly, pCR after NAT was also associated with improved survival (HR 0.22, 95% PI: 0.15–0.30). The association of pCR with improved EFS was similar among patients who received subsequent adjuvant chemotherapy (HR 0.36, 95% PI: 0.19–0.67) and those without adjuvant chemotherapy (HR 0.36, 95% PI: 0.27–0.54), with no significant difference between the two groups (p = 0.60). INTERPRETATION: Achieving pCR following NAT is associated with significantly better EFS and OS, particularly for triple negative and HER2+ breast cancer. The similar outcomes with or without adjuvant chemotherapy in patients who attain pCR likely reflects tumor biology and systemic clearance of micrometastatic disease, highlighting the potential of escalation/de-escalation strategies in the adjuvant setting based on neoadjuvant response.